Effectiveness of exercise interventions on sperm quality: a systematic review and network meta-analysis - Song, Weijia; Peng, Yu; Jiang, Zhuyu; Quan, Zheping (Frontiers in Endocrinology, 2025)
BackgroundInfertility affects about 10% to 15% of the world’s population, thus making it a global concern. Although there are a large number of studies to develop treatment for infertility in men, there are no studies to illustrate the effect of exercise on male sperm treatment in a well rationalized and aggregated manner, therefore the aim of this study was to validate the comparative effectiveness of different exercise interventions for treating sperm quality in men by using a network Meta-analysis.MethodsAll randomized clinical trials (RCT) were obtained from PubMed, Cochrane Library, EMBASE, Web of Science, CNKI, Wanfang, and VIP databases, and network meta-analysis was used to assess the effectiveness of exercise interventions on sperm quality.ResultsFourteen studies with 1079 subjects were finally included in this study. Compared with the physical inactivity group, indoor aerobic, outdoor aerobic, and resistance training significantly reduced sperm density (P<0.05); indoor aerobic, outdoor aerobic, and resistance training significantly reduced the number of necrotic spermatozoa and the number of active spermatozoa (P>0.05).Outdoor aerobic[MD=1.84,95%CI:(1.56,2.14),P<0.05], multi-component motion [MD=1.37,95%CI:(0.85,1.89),P<0.05],competitive sports[MD=1.04,95%CI:(0.46,1.60),P<0.05],indoor aerobic [MD=0.32, 95%CI:(0.21,0.44), P<0.05], effectively enhanced sperm volume; other sports [MD=9.49,95%CI:(6.17,12.84),P<0.05], indoor aerobic[MD=4.43,95%CI:(3.12,5.74),P<0.05],resistance training [MD=3.93, 95%CI:(0.49,7.37), P<0.05], competitive sports [MD=5.44,95%CI:(0.10,10.79), P<0.05], and bicycle aerobics[MD=27.29,95%CI:(22.45,32.06),P<0.05], significantly enhanced sperm motility; other sports [MD=17.20,95%CI:(3.12,31.19), P<0.05], effectively enhanced total sperm count;resistance training[MD=10.90,95%CI:(8.44,13.36), P<0.05],other sports [MD=1.97,95%CI:(1.41,2.54),P<0.05], indoor aerobic [MD=2.43,95%CI:(1.13,3.73), P<0.05],and bicycle aerobic [MD=12.18, 95%CI:(10.19,14.18),P<0.05], significantly enhanced sperm morphology; bicycle aerobic (MD=18.87, 95%CI:11.70,25.86, P<0.05), and indoor aerobic (MD=9.53, 95%CI:8.97,10.09, P<0.05),effectively enhanced sperm concentration.ConclusionIn conclusion, outdoor aerobics had a significant effect on improving sperm volume in infertile patients; other sports had a significant effect on enhancing sperm motility and total sperm count in infertile patients; resistance training had a significant effect on enhancing sperm morphology in infertile patients, and bicycle aerobic has a significant impact on improving sperm concentration in infertile patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#myprospero, identifier CRD42024534582.